“But are we going to deal with the hard questions?”: Waves of Compassion in Halifax Regional Municipality - Walsh, Susan; Gonzalez, Fabiana; Joy, Phillip; MacAulay, Kim (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2014)
Within broader social concern about compassion and learning to live well together in the world, a non-profit community-based organization called Waves of Compassion has emerged in Halifax Regional Municipality (HRM) in Nova Scotia, Canada. In this article, we explore how compassion relates to some “hard questions” that have arise for the organization—questions related to issues of marginalization and inclusivity: for example, what it might mean to “walk in another’s shoes,” particularly when that person or group of people is different from you in terms of age, race, ethnicity, sexual orientation, socioeconomic status, or citizenship. We also wonder what role the Waves organization might take up in terms of action and/or practice with regard to transforming inequity and promoting inclusivity in the community. We consider such questions in the context of data derived from a recent survey that Waves of Compassion undertook. We integrate found poems (many of which are derived from the survey data) and expository writing as means of underlining what some writers have said about compassion—that it involves both emotions and rational thought, the undoing of sharp distinctions between the two. We see compassion as a form of practice where boundaries and separations might be dissolved (at least at times) through being and knowing in different ways.